Feasibility Analysis of Opening Sempol Ayam Crispy MAW.IH Business In Bandung City Viewing From Market, Technical, and Financial Aspects - Faya Dwitifany; Nanang Suryana; Sinta Aryani (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
Sempol Ayam Crispy Maw.Ih outlet is a business engaged in the culinary field that will be opened in the city of Bandung using a take away service system. In this study, the market aspect was examined by distributing questionnaires to 100 respondents who were residents of the city of Bandung with an age range of 15-64 years. The results of the distribution of this questionnaire show that the percentage of the number of potential markets is 94%, the available market is 90%, and for the target market, Sempol Ayam Crispy Maw.Ih sets a target of 0.4% of the available market. For the technical and financial aspects, secondary data is used. obtained from several sources. The results of the projected feasibility calculation for five years show that the MARR percentage is 13%, the Net Present Value (NPV) is Rp.123.256.159, the Internal Rate of Return (IRR) is 59%, and the Pay Back Period (PBP) is 1 year. 9 months. Due to the NPV > 0, the IRR > MARR, and the PBP is not greater than the financial projection period, the opening of the Sempol Ayam Crispy Maw.Ih outlet is feasible. Sempol Ayam Crispy Maw.Ih outlet is a business engaged in the culinary field that will be opened in the city of Bandung using a take away service system. In this study, the market aspect was examined by distributing questionnaires to 100 respondents who were residents of the city of Bandung with an age range of 15-64 years. The results of the distribution of this questionnaire show that the percentage of the number of potential markets is 94%, the available market is 90%, and for the target market, Sempol Ayam Crispy Maw.Ih sets a target of 0.4% of the available market. For the technical and financial aspects, secondary data is used. obtained from several sources. The results of the projected feasibility calculation for five years show that the MARR percentage is 13%, the Net Present Value (NPV) is Rp.123.256.159, the Internal Rate of Return (IRR) is 59%, and the Pay Back Period (PBP) is 1 year. 9 months. Due to the NPV > 0, the IRR > MARR, and the PBP is not greater than the financial projection period, the opening of the Sempol Ayam Crispy Maw.Ih outlet is feasible.